Written in bones : how human remains unlock the secrets of the dead - Bahn, Paul G. (Firefly Books, 2003)
This book brings together a team of international experts to show how the careful study of bones and other ancient remains using modern scientific techniques, known as forensic archaeology, can reveal a picture of the lives, cultures and beliefs of ancient societies. Includes the Chinchorro mummies of Chile, Ötzi the Iceman, headless men and giant wolves from a Mesolithic cemetery in Siberia, burials from Han dynasty China, bog bodies from Denmark, and many others.